Value trace problems with assisting references for Python programming self-study - Hay Mar Shwe, San Hay Mar; Funabiki, Nobuo; Syaifudin, Yan Watequlis; Tar, Phyu Phyu; Kyaw, Htoo Htoo Sandi; Thant, Hnin Aye; Kao, Wen-Chung; Min, Nandar Win; Myint, Thandar; Htet, Ei Ei (International journal of Web information systems, 2021)
PurposeThis study aims to present the value trace problem (VTP) for Python programming self-study, by extending the works for Java programming learning assistant system. In total, 130 VTP instances are generated using Python codes in textbooks and websites that cover basic/advanced grammar topics, fundamental data structures and algorithms and two common library usages. Besides, assisting references on Python programming topics related to the VTP instances are introduced to assist novice learners in solving them efficiently.Design/methodology/approachPyPLAS offers the VTP to study grammar topics and library usage through code reading. A VTP instance asks a learner to trace the actual values of important variables or output messages in the given source code. The correctness of any answer is checked through string matching.FindingsThe applications to 48 undergraduate students in Myanmar and Indonesia confirm the validity of the proposal in Python programming self-studies by novice learners.Originality/valueThe applications to 48 undergraduate students in Myanmar and Indonesia confirm the validity of the proposal in Python programming self-studies by novice learners.